STRATEGI KEPEMIMPINAN DAN KINERJA ORGANISASI PERANGKAT DAERAH: BUKTI EMPIRIS DARI DINAS KETENAGAKERJAAN KABUPATEN BANDUNG - Mira Veranita (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Changes in the public sector environment require improved organizational performance supported by effective leadership strategies. In the context of local employment services, leadership plays a critical role in managing personnel and enhancing the quality of public service delivery. This study aims to analyze leadership strategies in improving organizational performance at the Local Employment Agency of Bandung Regency. The study employs a mixed methods approach with a sequential explanatory design. Quantitative data were collected through a questionnaire administered to 72 employees and analyzed using descriptive statistics and simple regression analysis. Qualitative data were obtained through in-depth interviews and observations to provide contextual understanding of leadership practices. The findings indicate that leadership strategies have a positive and significant effect on organizational performance. Leadership vision, decision-making, communication, motivation, and human resource management contribute to effectiveness, efficiency, service quality, and goal achievement. The study concludes that integrative and context-sensitive leadership is essential for improving the performance of local government organizations.